Analysis of the application of value engineering in the building construction project of State Elementary School 1 Padang Sambian - Matung, Ronaldi; Kumara, I Nyoman Indra; Indrashwara, Decky Cipta; Wedagama, Dewa Ayu Trisna Adhiswari (Privietlab, 2026)
Cost efficiency is an important aspect of project planning. One common approach to increasing cost efficiency is value engineering. This study applies Value Engineering to the Padang Sambian 1 Public Elementary School Building Construction Project with a total planned budget of IDR. 10,019,488,000.00. The analysis was conducted using the Dell'Isola method, which consists of four stages: information, creative, analytical, and recommendation. Based on the results of the study, the items carried out by Value Engineering include concrete work items on floors 1, 2, 3 and the roof, wooden plank truss work and roof tiles (roof work), door window hanging and locking work on floors 1, 2, and 3, masonry and plastering work (wall work) on floors 1, 2, and 3, paving block installation, ceramic floor and wall installation on floors 1, 2, and 3, and ceiling work on floor 3. The cost efficiency obtained using the Dell’Isola theory value engineering method is IDR. 224,566,091.39 or 2.24% of the total project cost with details of savings of IDR. 69,226,207.23 on concrete work on floors 1, 2, 3, and roof, IDR. 58,015,626.87 on truss work, wooden planks and roof tiles (roof work), IDR. 6,890,888.88 on door and window hanging and locking work on floors 1, 2, and 3, IDR. 1,160,097.63 on masonry and plastering work (wall work) on floors 1, 2, and 3, IDR. 48,561,507.2 on paving block masonry, IDR. 18,528,260.2 on ceramic floor and wall masonry on floors 1, 2, and 3, and IDR. 22,183,503.3 on the 3rd floor ceiling work. The benefits of applying value engineering are that it can reduce project costs without reducing the function, quality, and performance of the building, while providing a more efficient technical basis for decision-making at the planning and construction implementation stages.